Unraveling the Complexities of Severe Dengue: Exploring Transfusion Avoidance Strategies with Management of Hematological, Radiological Parameters, Clinical Features - Ranbeer Singh; Chhaviraj Singh; Swati Singh; Puja Singh (Clinical and Research Journal in Internal Medicine)
Background: Dengue is an entity caused by mosquito bites in humans. It can change into a life-threatening entity within a very short time. Not every dengue case requires a blood transfusion. While plasma leakage and a drop in platelet count are possible side effects of severe dengue, not all patients suffer from them. The main goals of treatment are to control symptoms such as pain, fever, and dehydration by giving patients enough fluids and medicine.